The Dialogue Decalogue: Ground Rule Interreligious, Interideological Dialogue - Leonard Swidler (Al-Jami'ah: Journal of Islamic Studies, 1994)
Dialogue is a conversation on a common subject between two or more persons with differing views, the primary purpose of which is for each participant to learn from the other so that he or she can change and grow. This very definition of dialogue embodies the first commandment of dialogue. In the religious-ideological sphere in the past, we came together to discuss with those differing with us, for example, Catholics with Protestants, either to defeat an opponent, or to learn about an opponent so as to deal more effectively with him or her, or at best to negotiate with him or her. If we faced each other at all, it was in confrontation-sometimes more openly polemically, sometimes more subtly so, but always with the ultimate goal of defeating the other, because we were convinced that we alone had the absolute truth. But dialogue is not debate. In dialogue each partner must listen to the other as openly and sympathetically as he or she can in an attempt to understand the other's position as precisely and, as it were, as much from within, as possible. Such an attitude automatically includes the assumption that at any point we might find the partner's position so persuasive that, if we would act with integrity, we would have to change, and change can be disturbing.